Normas voluntárias de sustentabilidade no comércio internacional: Aspectos teóricos, metodológicos e conceituais - Michelle Márcia Viana Martins; Danielle Mendes Thame Denny; Alicia Cechin; Scarlett Queen Almeida Bispo; Marcelo José Braga Nonnenberg; Flávio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Voluntary and private sustainability standards (VSS) are increasing its importance to manage value chain production: they are required by large multinational networks (mainly retailers) from their suppliers to optimize logistics and harmonize product characteristics; have been recognized as quality certificates to guarantee access to some more regulated markets with respect to environmental social and corporate criterias; and they have been used to prove that it meets more than the necessary legal requirements, reinforcing environmental social governance commitments voluntarily assumed by many companies. This paper describes VSS under different perspectives: i) their concepts, motivations and challenges; ii) the direct effects on trade and indirect effects on socio-environmental sustainability; iii) the transmission paths, retail networks and certifications; and iv) analyzes some empirical studies.
10419/284900
Keywords: Q17; Q51; Q56; 330; voluntary sustainability standards; VSS; international trade; certifications; trade and environment